Butyrate and glucose metabolism by colonocytes in experimental colitis in mice. Issue 4 (1st April 2000) - Ahmad, M S; Krishnan, S; Ramakrishna, B S; Mathan, M; Pulimood, A B; Murthy, S N
Abstract : BACKGROUND/AIMS: Impaired colonocyte metabolism of butyrate has been implicated in the aetiopathogenesis of ulcerative colitis. Colonocyte butyrate metabolism was investigated in experimental colitis in mice. METHODS: Colitis was induced in Swiss outbred white mice by oral administration of 4% dextran sulphate sodium (DSS). Colonocytes isolated from colitic and normal control mice were incubated with [ 14 C]butyrate or glucose, and production of 14 CO2, as well as of intermediate metabolites (acetoacetate, β-hydroxybutyrate and lactate), was measured. The effect of different substrate concentrations on oxidation was also examined. RESULTS: Butyrate oxidation (μmol/h per mg protein; mean (SEM)) was significantly reduced in DSS colitis, values on day 7 of DSS administration being 0.177 (0.007) compared with 0.406 (0.035) for control animals (p<0.001). Glucose oxidation (μmol/h per mg protein; mean (SEM)) on day 7 of DSS administration was significantly higher than in controls (0.06 (0.006) v 0.027 (0.004), p<0.001). Production of β-hydroxybutyrate was decreased and production of lactate increased in DSS colitis compared with controls. Increasing butyrate concentration from 10 to 80 mM enhanced oxidation in DSS colitis (0.036 (0.002) to 0.285 (0.040), p<0.001), although it continued to remain lower than in controls. Surface and crypt epithelial cells showed similar ratios of butyrate to glucose oxidation. When 1 mM DSS was added to normal colonocytes in vitro, it did not alter butyrate oxidation. The initial histological lesion of DSS administration was very patchy and involved crypt cells. Abnormal butyrate oxidation became apparent only after six days of DSS administration, at which time histological abnormalities were more widespread. CONCLUSIONS: Colonocyte metabolism of butyrate, but not of glucose, is impaired in DSS colitis, and may be important in pathophysiology. Histological abnormalities preceded measurable defects in butyrate oxidation.